Research and Analysis of Investment and Construction Activities in the Republic of Uzbekistan - S., Suyunov A.; A., Mirzaev Z.; M., Suyunova Ya. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The purpose of this article is to identify scientific and practical recommendations for enhancing and improving the efficiency of investment and construction activities carried out in the Republic of Uzbekistan. The paper also provides an assessment of positive and negative factors affecting the efficiency of investment and construction activities and a number of recommendations for improving the use of the production potential of construction organizations in the investment field.